The Role of the International Criminal Court in Law Enforcement against Public Health Crimes: Case Review and Implications - Miliyandra; Yogi Angistya Tamara; Mijan; Purnomo, Hadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the role of the International Criminal Court (PPI) in law enforcement against public health crimes through a review of relevant cases. By analyzing PPI involvement and its implications, this research aims to understand how PPI can influence law enforcement against public health crimes at the global level